The economics of imperfect competition - Robinson, Joan. (London : Macmillan and Co. Ltd., 1933)
Among persons interested in economic analysis, there are tool- makers and tool- users. This book is presented in analytical economist as a box of tools.
Includes index
II 15/01/2019
Loans
Keywords: Value; Monopolies; Competition; Prices; Economics, Mathematical